ANALISIS KESULITAN BELAJAR MATEMATIKA PADA SISWA KELAS V MI - Widayanti, Febi Dwi; Rahayuningsih, Sri; Yuliana, Fika; Christian, Steven (SCIENCE : Jurnal Inovasi Pendidikan Matematika dan IPA, 2025)
This study examines the difficulties in learning mathematics experienced by fifth grade students of MI Wahid Hasyim. The main objective is to identify the forms of difficulties and the factors causing them. The method used is descriptive qualitative with data collection through interviews, observations, written tests, and document studies. The research sample involved 22 students (10 males and 12 females) from fifth grade of MI Wahid Hasyim Pakis Malang. Data analysis was carried out in three stages: data reduction, presentation of results, and verification of conclusions. The research findings show that most students have not met the KKM (Minimum Completion Criteria), with the main obstacles including difficulty in understanding questions, weak mastery of mathematical concepts, inappropriate use of formulas and symbols, and limitations in problem-solving steps. The causes of these difficulties come from two aspects, namely internal factors (such as less active learning attitudes, intelligence levels, low motivation, and lack of interest in learning) and external factors (including family economic conditions, family relationship dynamics, curriculum policies, availability of learning media, school facilities, and the influence of the social environment). ABSTRAKPenelitian ini mengkaji kesulitan belajar matematika yang dialami siswa kelas V MI Wahid Hasyim. Tujuan utamanya adalah mengidentifikasi bentuk kesulitan serta faktor penyebabnya. Metode yang digunakan bersifat deskriptif kualitatif dengan pengumpulan data melalui wawancara, observasi, tes tertulis, dan studi dokumen. Sampel penelitian melibatkan 22 siswa (10 laki-laki dan 12 perempuan) dari kelas V MI Wahid Hasyim Pakis Malang. Analisis data dilakukan melalui tiga tahap: reduksi data, penyajian hasil, dan verifikasi kesimpulan. Temuan penelitian menunjukkan bahwa sebagian besar siswa belum memenuhi KKM (Kriteria Ketuntasan Minimum), dengan hambatan utama meliputi kesulitan memahami soal, lemahnya penguasaan konsep matematika, penggunaan rumus dan simbol yang tidak tepat, serta keterbatasan dalam langkah penyelesaian masalah. Penyebab kesulitan ini berasal dari dua aspek, yaitu faktor internal (seperti sikap belajar kurang aktif, tingkat kecerdasan, motivasi rendah, dan kurangnya minat belajar) dan faktor eksternal (termasuk kondisi ekonomi keluarga, dinamika hubungan keluarga, kebijakan kurikulum, ketersediaan media pembelajaran, fasilitas sekolah, serta pengaruh lingkungan sosial).